TOMO Hugglink - Andersson, Tobias
Tomo Hugglink (TOMO Skog) is an innovation for harvest and transport of biofuels. The system consists of a truck, a chipping unit and crane mounted on a link and a wood chip trailer. The system works in such a way that the chipping unit is disconnected and placed on the site and wood chips are loaded directly into the wood chip trailer. The aim of this study was: - To examine the performance of the TOMO Hugglink system under different conditions such as the size, placement and quality of the pile. - To calculate the cost per raw ton for two vehicle combinations at different transport distances and to examine the effect of a reduction in set-up time and an increase in load weight. - To identify possible improvements with the TOMO Hugglink system. A time study was conducted within the thesis work to make it possible to determine production and time consumption. In the subsequent economic analysis the cost per tone at different transport distances was calculated for two different lorry concepts. Furthermore the effect of a reduction in set-up time and an increase in load weight was calculated. Under current conditions the utilization of the chipper is low and only 29 % of the total system time is occupied by chipping. This problem can be remedied by adding another truck and chip trailer to the system. According to estimates the cost per tone can be reduced for objects with transport distances longer than 34 km by adding another truck and trailer. An increase in load weight can reduce the cost for the system and the impact is greatest on long transport distances. An increase in load weight from 25, 6 tons to 28 tons results in the configuration with one truck and trailer having lowest cost up to a transport distance of 37 km. By reducing the set-up time by 20 % the cost can be lowered and the configuration with two trucks and two trailer are cost efficient up to a transport distance of 31 km.